2010
DOI: 10.3340/jkns.2010.47.2.143
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Lumbar Metastasis of Choriocarcinoma Masquerading as an Extraosseous Extension of Vertebral Hemangioma

Abstract: We report here on an uncommon case of metastatic choriocarcinoma to the lung, brain and lumbar spine. A 33-year-old woman was admitted to the pulmonary department with headache, dyspnea and hemoptysis. There was a history of cesarean section due to intrauterine fetal death at 37-weeks gestation and this occurred 2 weeks before admission to the pulmonary department. The radiological studies revealed a nodular lung mass with hypervascularity in the left upper lobe and also a brain parenchymal lesion in the parie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Choriocarcinoma is associated with molar pregnancy, a rapid rate of hematogenous spread to multiple organs and increased levels of β-human chorionic gonadotropin (β-HCG), and is also associated with a positive response to chemotherapy (2,3). Choriocarcinoma primarily occurs in females of childbearing age and is rarely observed subsequent to menopause (1).…”
Section: Introductionmentioning
confidence: 99%
“…Choriocarcinoma is associated with molar pregnancy, a rapid rate of hematogenous spread to multiple organs and increased levels of β-human chorionic gonadotropin (β-HCG), and is also associated with a positive response to chemotherapy (2,3). Choriocarcinoma primarily occurs in females of childbearing age and is rarely observed subsequent to menopause (1).…”
Section: Introductionmentioning
confidence: 99%
“…1,6,8,9,15 There are reports on the rapid onset of signs of VH in the third trimester of pregnancy, suggesting that growth of the hemangioma can be stimulated by elevated secretion of estrogen with contribution of increased intraabdominal pressure. 3,8,9,15,16 To the best of our knowledge, spontaneous malignant transformation of VHs has not been reported. 2,3,8 According to criteria highlighted by Laredo and colleagues, aggressive VHs most frequently affect vertebrae from T-3 to T-9 and involve the entire VB, pedicles, and vertebral arch.…”
Section: Discussionmentioning
confidence: 99%
“…2, 16 We chose surgical removal of the compressive lesion from the spinal canal. The major complication associated with surgical removal of VHs is extensive blood loss.…”
mentioning
confidence: 99%
“…GTDs encompass a varied group of neoplastic disorders that arise from the trophoblastic epithelium of the placenta, characterised by a distinct tumour marker (β-HCG) [1, 2]. GTDs are conventionally subclassified into five distinct groups on the basis of their histopathologic, cytogenetic, and clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…Choriocarcinoma is a rare and highly malignant neoplasm of trophoblastic origin among the GTDs. This tumour is known for its association with molar pregnancy, a rapid haematogenous spread to multiple organs, high HCG levels and a good response to chemotherapy [2, 3]. It is preceded by several clinical conditions, it is observed that about 50% arise in molar pregnancies, 25% arise after previous abortions, 22.5% arise in normal pregnancies, and 2.5% arise subsequent to ectopic pregnancies [1–4].…”
Section: Discussionmentioning
confidence: 99%